The World's Smallest Papillary Thyroid Microcarcinoma: A 1.9 Millimeter-Diameter - Tarro, Giulio; Trapanese, Ersilio (British Journal of Healthcare and Medical Research, 2022)
This study investigated the usefullness of the Sonography, Superb Micro-Vascular Imaging and FNAC for the risk papillary thyroid microcarcinoma (PTMC). We report a case of a 30 -year-old Caucasian man affected by a papillary thyroid microcarcinoma (PTMC) of the right lobe of the thyroid gland with very tiny size of a 1.9-mm-diameter. The characteristics with the Diagnostic Imaging using Ultrasonography (US), Superb Micro-Vascular Imaging (SMI) and fine-needle- aspiration cytology (FNAC) are discussed. Ultrasonography, (SMI) and FNAC have proven to be the most sensitive diagnostic combination for the early detection of thyroid cancer. Despite tiny size of this nodule, associated with malignant cytology at FNAC represents an important biological risk factor and could predict possible for neck lymph node metastases (LNM).